Europa en la Globalización: puntos fuertes y débiles. - Palacio Morena, Juan Ignacio (Papeles del Este, 2007)
Globalization involves a growing process of productive integration on a world scale. In that process the key to competition lies with the capacity of knowledge and control of information that facilitates innovation. The European Union possesses initial advantages in order to achieve the goal that globalization involves, derived from its economic and monetary integration and the level of research and technological development to a great deal in the countries that it is comprised of. Nevertheless, it does not have an educational system and research developed on a European scale nor a clear international strategy with respect to neighboring groups of nations (for example, Africa and Euro-Asia ) There continues to be encouragement of a very intensive growth model based on capital with a progressive cutback on labor costs instead of one based on innovation and a strategic approach for the development of Africa and Eastern Europe which are not integrated in the European Union.